2012
DOI: 10.3109/00498254.2012.675095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human cytochrome P450 isoforms and esterases involved in the metabolism of mirabegron, a potent and selective β3-adrenoceptor agonist

Abstract: 1. Human cytochrome P450 (CYP) enzymes and esterases involved in the metabolism of mirabegron, a potent and selective human β(3)-adrenoceptor agonist intended for the treatment of overactive bladder, were identified in in vitro studies. 2. Incubations of mirabegron with recombinant human CYP enzymes showed significant metabolism of mirabegron by CYP2D6 and CYP3A4 only. Correlation analyses showed a significant correlation between mirabegron metabolism and testosterone 6β-hydroxylation (CYP3A4/5 marker activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…7,16 In addition, cytochrome 450 (CYP) 3A4 is the primary isoenzyme responsible for the hepatic oxidative metabolism of mirabegron in vitro, with a minor role of CYP2D6. 16 Mirabegron is cleared by multiple metabolic enzymes with no single enzyme dominant.…”
Section: Clinical Therapeutics 1040mentioning
confidence: 99%
See 1 more Smart Citation
“…7,16 In addition, cytochrome 450 (CYP) 3A4 is the primary isoenzyme responsible for the hepatic oxidative metabolism of mirabegron in vitro, with a minor role of CYP2D6. 16 Mirabegron is cleared by multiple metabolic enzymes with no single enzyme dominant.…”
Section: Clinical Therapeutics 1040mentioning
confidence: 99%
“…In study 2, urine samples for measurement of unchanged mirabegron were collected no more than 12 hours before dosing and from 0 to 12 hours, 12 to 24 hours, 24 to 48 hours, 48 to 72 hours, and 72 to 96 hours after dosing. In studies 4 and 5, blood samples were collected before dosing and at 0.5, 1, 2, 3, 4, 5, 6,7,8,12,16,24,36,48,72, and 96 hours after dosing in the single-dose period and on the final day in the multiple-dose period, before the first administration of study drug in the multiple-dose period, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 12, 16, and 24 hours after dosing on the first day in the multiple-dose period, and before dosing on days 5, 6, and 7 in the multiple-dose period. Plasma was collected by centrifugation, and plasma and urine samples were stored at -651C or below until analysis.…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The reaction was initiated by the addition of PNPA after a 2-minute preincubation at 37°C. The preincubation time referred to previous reports (Karanth and Pope, 2000;Takusagawa et al, 2012;Yanjiao et al, 2013;Ohura et al, 2014). After a 1-minute incubation at 37°C, the reaction was terminated by the addition of 100 ml of ice-cold methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Butyrylcholinesterase exists in human plasma. Jbilo et al (1994) reported that butyrylcholinesterase mRNA was detected in human liver, but the enzyme activity appeared to be undetectable in the liver as well as in intestinal fractions (Takusagawa et al, 2012). Taken together, if a drug is found to be hydrolyzed by human liver microsomes, the enzymes responsible for the hydrolysis are likely CES or AADAC.…”
Section: Introductionmentioning
confidence: 99%
“…At steady state, mirabegron shows a large volume of distribution of 1670 l [52]. The metabolism of mirabegron is mainly due to the liver; in particular, it is metabolized by different metabolic pathways such as N-dealkylation, oxidative metabolism catalysed by CYP 3A4/5 [54], with a minor role for CYP2D6, amide hydrolysis by esterases and uridine diphosphateglucuronosyltransferases-mediated glucuronidation [55]. At least 10 metabolites are derived from liver metabolism of mirabegron, but none of them has pharmacological activity [55].…”
Section: Pharmacokineticsmentioning
confidence: 99%